Onderwysersopleiding in Suid-Afrika : leersame aspekte van ander stelsels - Van der Walt, Johannes L.; Potgieter, F.J.; Wolhuter, C.C. (Buro vir Wetenskaplike Tydskrifte / Potchefstroom, 2009)
Multigrade classrooms face a lot of challenges because of their unique circumstances where more than one grade is combined in one classroom with one teacher. One of the problems is the lack of suited teaching and learning materials (TLM) for these classrooms. It includes the lack of computer-based TLM. Existing TLM that is developed for the use in monograde classroom cannot be used effectively in multigrade classrooms. TLM can provide a valuable contribution in these unique teaching and learning processes. An investigation was needed to determine the condition of die development, selection and use of TLM in these kind of schools. Only then can the solutions for the problems be investigated. During the investigation quantitative and qualitative research methods were used. During the first phase data was collected by a structured questionnaire where after and where of data were collected through standardized structured open-ended interviews and classroom observations in phase two and three. One of the main reasons for the problem is multigrade teacher‟s lack of knowledge and skills in die development, selection and use of TLM in the teaching and learning process. There are no criteria and requirements for the development and selection of TLM. Multigrade teachers do no realize the contribution TLM can provide in the process. The teaching strategies used in the multigrade classroom are very teacher-centered and it contributes to learners‟ lack of development in die teaching and learning process. It also contributes to the multigrade teacher’s raise in work load and lack of time to do what they must do to ensure quality teaching and learning. There is big need for teacher training as well as in-service training of multigrade teachers that prepare teachers for the different aspects multigrade education. This training must not just include the development, selection and use of TLM, but also the five areas of multigrade teaching. Complete criteria and requirements for TLM in multigrade classroom must be composed by all the role players where after and where of TLM can be developed and selected effectively.